Combustion synthesis and upconversion luminescence properties of Er3+, Yb3+ doped gadolinium oxide nanophosphor - Tamrakar, Raunak kumar; Bisen, D P; Brahme, Nameeta (Recent Research in Science and Technology, 2012)
Gd2O3: Er3+, Yb3+ Nanophosphor prepared by combustion synthesis method. Optical and Upconversion luminescence properties of rare earth doped nanophosphors were studied. The nanophosphors were characterized using Scanning electron microscopy, X-ray diffraction and ultraviolet–visible absorption spectroscopy. The results of XRD show cubic phase can be obtained, the average crystalline size could be calculated as 38 and 49nm respectively, which coincided with the results from SEM images. The UV- Vis optical spectra were also studied. Upconversion luminescence spectra of samples under the range of 980 nm, excitation were investigated. The strong red and weak green emission was observed. The possible upconversion luminescence mechanisms for Er3+, Yb3+ doped gadolinium nanophosphor were also discussed.